Study of the interaction of lactoferricin B with phospholipid monolayers and bilayers - Arseneault, Marjolaine (Langmuir : the ACS journal of surfaces and colloids, 2010)
Bovine lactoferricin (LfcinB) is an antimicrobial peptide obtained from the pepsin cleavage of lactoferrin. The activity of LfcinB has been extensively studied on diverse pathogens, but its mechanism of action still has to be elucidated. Because of its nonspecificity, its mode of action is assumed to be related to interactions with membranes. In this study, the interaction of LfcinB with a negatively charged monolayer of dipalmitoylphosphatidylglycerol has been investigated as a function of the surface pressure of the lipid film using in situ Brewster angle and polarization modulation infrared reflection absorption spectroscopy and on transferred monolayers by atomic force microscopy and polarized attenuated total reflection infrared spectroscopy. The data show clearly that LfcinB forms stable films at the air-water interface. They also reveal that the interaction of LfcinB with the lipid monolayer is modulated by the surface pressure. At low surface pressure, LfcinB inserts within the lipid film with its long molecular axis oriented mainly parallel to the acyl chains, while at high surface pressure, LfcinB is adsorbed under the lipid film, the hairpin being preferentially aligned parallel to the plane of the interface. The threshold for which the behavior changes is 20 mN/m. At this critical surface pressure, LfcinB interacts with the monolayer to form discoidal lipid-peptide assemblies. This structure may actually represent the mechanism of action of this peptide. The results obtained on monolayers are correlated by fluorescent probe release measurements of dye-containing vesicles made of lipids in different phases and support the important role of the lipid fluidity and packing on the activity of LfcinB